Manajemen Marah dan Urgensinya dalam Pendidikan - Moch. Sya'roni Hasan (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2017)
Anger can be managed by controlling the wrath, forgiving someone mistake, doing ihsan to the one who has tortured, praying and simple in action. By having good capability in controlling anger well, means they have accomplished personal intelligence in fostering good relation with other. In this case they are able to be good person individually and socially. In other words, they have not only “sajadah ilahiyyah”, but also “sajadah insaniyyah” which is upheld by yang al-Qur’an that’s called Habl Min Allah wa Habl Min al-Nas. This is appropriate with the function Islamic education that is instilling good character in the children soul when they are growing up by direction and advice. So that their moral becomes one of their capability seeped their soul in the form of virtue, kindness and like to work for the benefit of the country.